Design and simulation of simple miniature devices for differentiation of airborne particles - Mohammad Ilyas Bin Mohammad Taib (Nanyang Technological University, 2022)
With the invention of the cascade impactor in the 1970s, coupled with the application of high-speed computers and finite difference methods, a deeper understanding has been developed with regards to the flow field and particle trajectories within impactors. Extensive studies in the 1970s have shown that impactors are able to provide accurate particle size classifications with sharp cutoff characteristics with the proper settings. This has led the impactor to be considered as a standard instrument for particle aerodynamic size analysis and classification. Thus, since the 1970s, the design of impactors have been constantly modified and improved upon based on the pre-established guidelines resulting from past theoretical studies. In this modern age of technology, newer methods of particle aerodynamic size analysis and classification are currently being developed, particularly with the aid of microelectronics to significantly reduce the size of particle differentiation devices. In this project, we explore several possible new designs for a microelectronics-based particle aerodynamic size differentiation device. However, since this field of study is relatively new, there are not many previously published literature available. As such, several studies are first conducted with regards to particle dynamics within a micro-channel. After which, modifications to the channel designs are made and step-by-step design and testing procedures are formulated to facilitate future works. Additional discussions are made relating to the design and simulation of the device.